Handling of generated hospital accustomed to residuals for the veterinary centers of Machala city, Ecuador - Pérez Rodríguez, Jhonny Edgar (2017)
This research paper is aimed at informing the results of a study conducted in 15 veterinarian centers located in Machala, El Oro province, Ecuador; in which physical, chemical, and microbiological properties of solid waste, that might have an impact on the environment and human health were analyzed. Random sampling, as well as systematic sampling was used in order to determine amount, humidity, density, and physical, physicochemical, microbiological composition of waste. The results allowed the researchers to determine the composition of waste generated by these veterinarian centers. Medical waste was found as predominant with 48%. It was also found the percentage of calorific capacity described as high in the majority of the veterinarian centers, as well as the microbiological characteristics, in which a high amount of mesophilic and pseudomona bacteria was established through leachate in all of the veterinary centers of the city.Said results will allow the development of strategies to improve the management of waste and biosecurity.